Canadian Pentecostalism: transition and transformation - Wilkinson, Michael (McGill-Queen's studies in the history of religion, 2009)
Pentecostalism in Canada: an introduction / Michael Wilkinson -- Origins and development -- Aspects of the Canadian pentecostal experience -- Institutionalization and globalization. - Bringing together a previously scattered and somewhat hidden literature, Canadian Pentecostalism provides the first comprehensive overview of the subject. The collection is broad in focus, examining classical Pentecostalism, charismatic movements in the Roman Catholic and mainline Protestant traditions, and neo-Pentecostalism. Contributing authors examine historical debates about the origins of the movement, the response of Pentecostalism to institutionalization and globalization, and the roles of women, aboriginals, and immigrants within the Canadian movement. --from publisher description